WRITING ARGUMENTATIVE ESSAY IN ONLINE ACADEMIC WRITING CLASS: STUDENTS’ VOICE, DIFFICULTIES, AND WRITING ENJOYMENT - Dedeh Rohayati; Andi Rustandi (Yayasan Akrab Pekanbaru, 2021)
The present study is aimed at finding out 1) students’ voices and their difficulties towards Academic Writing, and 2) students’ awareness of Argumentative essay. This study employs a qualitative case study involving twelve six semester students of English Department and enrolling Academic Writing course. The class is conducted online using Google Meet. The participants are selected purposively and divided into two category: six students with six years writing enjoyment and six students with three years writing enjoyment. The primary data are obtained through semi structured interview and students’ document Argumentative text conducted online. The result of interview are transcribed, categorized, coded, and interpreted. Meanwhile, the students’ document of Argumentative text are analyzed by utilizing the generic structure checklist of argumentative essay adopted from Derewianka (1990). The findings reveals that all of students perceived Academic Writing positively. Meanwhile, all of students’ writing ability are hampered by their less ability in organizing idea systematically, grammar, vocabulary and diction. Specifically, students who have six years writing enjoyment faces difficulties in Academic writing due to their lack of understanding the instruction and managing assignment. In contrary, the students with three years writing enjoyment find Academic Writing difficult due to low management of revision and less enthusiastic and motivation. The result of students’ document of Argumentative texts indicate that students’ awareness on Argumentative essay still need improvement. It is recommended for the further research on related topic to investigate the novel cases using the different method.